PENGARUH INDIKATOR MIKROPRUDENSIAL, MAKROPRUDENSIAL, DAN FINTECH TERHADAP STABILITAS SISTEM KEUANGAN DI INDONESIA - Chrissendy , Rafael; Saraswati, Birgitta (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Financial stability is a crucial element in the effectiveness of monetary policy, because without stability in the financial sistem, monetary policy transmission cannot run optimally. Therefore, Bank Indonesia and the Financial Services Authority/OJK have an important role in maintaining financial system stability through various policies implemented. This study aims to identify the influence of microprudential, macroprudential, and fintech variables on the stability of the Indonesian financial system. Using the Vector Error Correction Model method. The results showed that microprudential variables: Capital Adequacy Ratio/CAR and Loan to Deposit Ratio/LDR, have an influence on financial system stability. From the macroprudential aspect, composite stock price index, inflation, and exchange rate proved to have a significant effect on financial system stability. Meanwhile, fintech variables such as ATM/Debit and credit card have an effect on financial system stability. Moreover, shocks to composite stock price index, exchange rate, and inflation are permanent, while CAR, LDR, e-money, ATM/Debit, and credit card variables cause financial system stability imbalances in the next eight quarters. The implication of this study confirms that BI, OJK, and related policy makers play a strategic role in maintaining and improving the stability of Indonesia's financial system.